THE PLACE OF THROMBOPHILIA WITHIN THE STRUCTURE OF THE FETAL LOSS SYNDROME IN WOMEN WITH METABOLIC SYNDROME - T. B. Pshenichnikova; E. B. Perederyaeva; E. B. Donina; Z. K. Gadaeva (IRBIS LLC, 2016)
Metabolic syndrome is commonly found among women of reproductive age and represents a risk factor for various pregnancy complications. The presence of genetically determined hypofibrinolysis in women with metabolic syndrome, along with other forms of thrombophilia, determines the implantation failure and abnormalities in trophoblastinvasion and placentation. Subsequently, this may cause the fetal loss syndrome and other pregnancy complications.